Pediatric Heart Transplantation Long-Term Survival in Different Age and Diagnostic Groups: Analysis of a National Database. (May 2017) - Alsaied, Tarek; Khan, Muhammad S.; Rizwan, Raheel; Zafar, Farhan; Castleberry, Chesney D.; Bryant, Roosevelt; Wilmot, Ivan; Chin, Clifford; Jefferies, John L.; Morales, David L.
Background: The purpose of this study was to evaluate differences in long-term survival without the influence of early mortality, and to identify factors associated with one-year conditional ten-year survival after heart transplantation (HTx) across different age and diagnostic groups. Methods: Organ Procurement and Transplant Network data from January 1990 to December 2005 were used. Cohort was divided according to age (infants [<1 year], children [>1-10 years], and adolescents [11-18 years]) and diagnosis (cardiomyopathy and congenital heart disease [CHD]). Factors associated with one-year conditional ten-year survival were identified using multivariable logistic regression and using a case–control design. Results: One-year conditional ten-year survivors included 1, 790 patients compared to 1, 114 patients who died after the first posttransplant year and within ten years of transplant with a median follow-up of 4.8 years. Predictors of one-year conditional ten-year survival for infants were recipient's Caucasian race (odds ratio [OR]: 1.9, 95% confidence interval [CI]: 1.3-2.7) and donor–recipient weight ratio (OR: 0.8, 95% CI: 0.6-1); for children: Caucasian race (OR: 1.6, 95% CI: 1.2-2.1), retransplantation (OR: 0.4, 95% CI: 0.2-0.6), and transplantation after the year 2000 (OR: 1.5, 95% CI: 1.1-2.1); for adolescents only Caucasian race (OR: 2.5, 95% CI: 1.9-2.3). In both CHD and cardiomyopathy, adolescents had worse survival compared to infants and children. There was an era effect with improved survival after 2000. Male gender was a predictor of survival in cardiomyopathy group. Conclusion: Predictors of one-year conditional ten-year survival varied among groups. These data and analyses provide important information that may be useful to clinicians, particularly when counseling patients and families regarding expectations of survival after pediatric HTx.